The Concept of Maqashid Sharia According to Ibn Taymiyyah and Ibn Qayyim Al-Jauziyah and Its Implementation in Economics - Muhammad Faiq Abdullah Syafie; Muhajirin Muhajirin (Journal of Islamic Economy, 2025)
Ibn Taymiyyah and Ibn Qayyim al-Jawziyyah were influential Islamic scholars and thinkers who shared a mentor-student relationship. Both scholars contributed significantly to the discourse on maqasid al-shariah (objectives of Islamic law) and Islamic economics. This study aims to explore their perspectives on maqasid al-shariah and its application in economics. A qualitative descriptive method was employed, with data collection through an extensive literature review. The findings reveal that Ibn Taymiyyah categorized maqasid al-shariah into three main components: al-maqsud al-‘azam (the supreme objective), al-maqasid al-asasiyyah (the fundamental objectives), and al-maqasid al-furuiyah (the subsidiary objectives). Conversely, Ibn Qayyim al-Jawziyyah categorized maqasid al-shariah into three classifications: ta’lil al-ahkam (rationale of rulings), daruriyyat al-khams (the five essentials), and taghayyur al-fatwa wa ikhtilafuha (variation in legal opinions) based on changes in time, place, circumstances, intentions, and customs. In the context of economics, Ibn Taymiyyah emphasized the practical application of maqasid al-shariah in market mechanisms, price regulation, and property rights. Meanwhile, Ibn Qayyim al-Jawziyyah focused on the philosophical dimensions of Islamic economics, addressing issues such as wealth distribution, poverty alleviation, and the economic significance of zakat